Anmerkungen zu den hochdeutsch überlieferten Volksballaden in der Sammlung aus der Gottschee - Holzapfel, Otto (Traditiones (Ljubljana), 1999)
The author has ascertained that numerous folk ballads from Ko!čevsko are sung not only in dialects, but also in literary German. Some notes also reveal a mixture of the dialect and the literary language. Further analysis leads to the conclusion that all ballads from this area which are sung in dialects are not as ĆoldĆ as they seem and that, likewise, all the texts in the literary language are not as ˝new˝ as they may seem.
Keywords: Ethnopoetics; ljudske pesmi; slovstvena folklora